“Neonato Con Sindrome De Aspiración De Liquido Meconial Del Hospital Sagrado Corazón De Jesús De Quevedo” - Banchen Riofrio, Ana Gabriela (2019)
Meconium aspiration syndrome is a breathing disorder, given the aspiration of meconium in the amniotic fluid, meconium corresponds to first eliminate. Lee by a baby shortly after birth, until the baby begins to milk. In some cases eliminates meconium while still in utero, this can happen when babies are under stress given to the blood supply and oxygen decreases. Meconium can also obstruct the airway of the baby immediately after birth. This can cause breathing problems due to swelling of the lungs of the baby after the birth. The methodology used was emphasized to the investigation of the causes of clinical picture, treatments and diagnoses of Pathology, several data collection methods were used for this: physical assessment by systems, functional health patterns and dysfunctional Marjory Gordon, this were drawn up nursing diagnoses related to observed conditions and interventions implemented in order to improve the health status of the infant patient.